Features of Roasted Green Coffee Beans: A Review - Das, Monalisa; Mohanty, S N (International Journal of Psychosocial Rehabilitation, 2025)
The advancement of food preparation component installations involves the assessment of the mechanical features of food components. The understanding of customers as well as the layout specifications of manufacturing equipment is influenced by features such as the length, structure and color. Liquid movement, humidity, density and resting angle. During this study, improvements in microwave defrosting variables analyzed the technology characteristics of green/unroasted coffee beans. The system variables were roasted energy (300, 450, 600 W) including time (5.0, 10.0, 15.0, &20.0 min) and the coffee beans were evenly spread with such a sequence of cooking. Satisfactory roasting with a signature coffee pink color, was deemed achieved. Water behavior of the potatoes has been identified under safe, laboratory limits (aw